The environmental and organizational determinants of county prosecutor salaries - Choi, Myunghyun (Journal of crime and justice, 2023)
National surveys show that criminal justice organizations must devote considerable energy to recruiting qualified personnel and, in some cases, they struggle to attract sufficient applicant pools. To address these problems, organizations may use salary as a means of attracting candidates. From a contingency theory perspective, pay should be higher when the demands of the work and the nature of the organizational environment serve as detractors to successful recruitment. Using data from national surveys of prosecutor offices, this study explores the relationship between salary, the environment, and the organization. Results suggest that prosecutor pay is consistently related to county cost of living and, in different analytical models, caseload, government form, community conservatism, and rurality. The implications for theory and policy are discussed.